Do Local or Foreign traders know more in an emerging market? A possible solution of the puzzle. (2007)
A branch of the literature in international finance has tried to give a definitive answer to the question, who is better informed in an emerging market, Foreigners or Locals?. We measured the probability of informed trading (PIN) for the Jakarta Stock Exchange for two types of investors, foreigners and locals, developing an extension of the model of Easley, Kiefer and O’Hara (1997). We find that locals do most of the informed trades, but also most of the uninformed trades. On the other hand, given the type of investor, foreigners are more likely to be informed than locals. Besides, the evidence shows that locals tend to be more informed in smaller and more volatile firms, whereas foreigners tend to be more informed in larger an less volatile firms and firms with higher foreign ownership. We also find evidence of market-wide effects on liquidity from the foreign informed trades but not from the local ones.